Five-year outcome of respiratory muscle weakness at intensive care unit discharge: secondary analysis of a prospective cohort study. Issue 6 (12th March 2021) - Van Aerde, Nathalie; Meersseman, Philippe; Debaveye, Yves; Wilmer, Alexander; Gunst, Jan; Casaer, Michael P; Wauters, Joost; Wouters, Pieter J; Gosselink, Rik; Van den Berghe, Greet; Hermans, Greet
Abstract : Purpose: To assess the association between respiratory muscle weakness (RMW) at intensive care unit (ICU) discharge and 5-year mortality and morbidity, independent from confounders including peripheral muscle strength. Methods: Secondary analysis of the prospective 5-year follow-up of the EPaNIC cohort (ClinicalTrials.gov: NCT00512122 ), limited to 366 patients screened for respiratory and peripheral muscle strength in the ICU with maximal inspiratory pressure (MIP) after removal of the artificial airway, and the Medical Research Council sum score. RMW was defined as an absolute value of MIP <30 cmH2 O. Associations between RMW at (or closest to) ICU discharge and all-cause 5-year mortality, and key measures of 5-year physical function, comprising respiratory muscle strength (MIP), hand-grip strength (HGF), 6 min walk distance (6MWD) and physical function of the SF-36 quality-of-life questionnaire (PF-SF-36), were assessed with Cox proportional hazards and linear regression models, adjusted for confounders including peripheral muscle strength. Results: RMW was present in 136/366 (37.2%) patients at ICU discharge. RMW was not independently associated with 5-year mortality (HR with 95% CI 1.273 (0.751 to 1.943), p=0.352). Among 156five-year survivors, those with, as compared with those without RMW demonstrated worse physical function (MIP (absolute value, cmH2 O): 62(42–77) vs 94(78–109), p<0.001; HGF (%pred): 67(44–87) vs 96(68–110), p<0.001; 6MWD (%pred): 87(74–102) vs 99 (80–111), p=0.009; PF-SF-36 (score): 55 (30–80) vs 80 (55–95), p<0.001). Associations between RMW and morbidity endpoints remained significant after adjustment for confounders (effect size with 95% CI: MIP: −23.858 (−32.097 to −15.027), p=0.001; HGF: −18.591 (−30.941 to −5.744), p=0.001; 6MWD (transformed): −1587.007 (−3073.763 to −179.253), p=0.034; PF-SF-36 (transformed): 1.176 (0.144–2.270), p=0.036). Conclusions: RMW at ICU discharge is independently associated with 5-year morbidity but not 5-year mortality.